Physiological response and phytoremediation potential of dioecious Hippophae rhamnoides inoculated with arbuscular mycorrhizal fungi to Pb and Zn pollution - Fang, Ling; Zeng, Zhenxiong; Jia, Qi; Lin, Yuhu; Chen, Hao; He, Yunxiao; Chen, Juan (Frontiers in Plant Science, 2024)
Plant-microorganism combined remediation of heavy metal pollution has been reported, but little attention has been paid to the effect of arbuscular mycorrhizal (AM) fungi on phytoremediation of dioecious plants under heavy metal pollution. In this study, the growth, physiological responses and phytoremediation traits of Hippophae rhamnoides were determined to evaluate whether sex-specific ecophysiological responses and phytoremediation capacities of females and males are affected by additional AM fungi (Glomus mosseae) under heavy metal treatments. The results showed that excess Pb and Zn stresses inhibited photosynthetic capacities of both sexes. However, inoculated AM fungi treatment increased the activity of photosynthesis, content of photosynthetic pigment, activity of superoxide dismutase, the content of proline and root Pb content and enrichment coefficient of males while decreased root Pb content of females under Pb stress. On the other hand, inoculated AM fungi treatment increased the photosynthetic activities and Pro accumulation of females, and activity of superoxide dismutase and transport coefficient of males under Zn stress. These results demonstrate that H. rhamnoides inoculated AM fungi showed significant sex-specific responses on the growth, physiological traits and phytoremediation potential to Pb and Zn stress. AM fungi significantly improved the tolerance of males to Pb stress and both sexes to Zn stress, which indicates H. rhamnoides and AM fungi can be used as a plant-microbial combined remediation method for Pb and Zn contaminated soil. More attention should be paid on sexual-specific responses and phytoremediation of dioecious plants to heavy metals in the future.